The Incertitude of Language and Life in the Poetry of Olvido García Valdés - Sharon Keefe Ugalde (Studies in 20th & 21st Century Literature, 2012)
Two of Ludwig Wittgenstein’s formulations serve as guideposts for the analysis of the poetry of García Valdés: the concept of language-game and the Creation Mystic Experience, or seeing the world as a miracle. The paper first considers the language-game in terms of “unbound” or exempt language. The poet, recognizing the metamorphic nature of language, frees it from predetermined cultural content and, most notably, from grammatical rigidity, toying with ambiguity and fluidity through such techniques as juxtaposition, pronoun vagueness and ellipsis. The second part of the study considers the poet’s exploration of the ineffable, which embraces both the astonishment of being alive in the world—a mystic experience—and the mystery of death. The discovery of the wondrousness of the real comes through unhurried observation—principally visual, but also auditory and tactile—and is expressed with poignancy in language exempt from conventional constraints. When the focus is on mortality, additional textual strategies are present, for example, locating death in the body and placing a single sound within vast silence. What predominates is neither the astonishment of the real nor the menacing nearness of death but tension between the two; the ineffable balances on an axis of chiaroscuro.
Keywords: Olvido García Valdés; poetry; poetic strategy; mystic; language; mortality; life; death; chiaroscuro